Perancangan Sistem Pentanahan Gedung Pusat Komputer Universitas Negeri Manado - Jeferson Yalindua; Billy Kilis; Herry Sumual (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2022)
This study aimed to design a grounding system in the Computer Center Building and analyze the feasibility of the building in the use of a lightning rod system. This research was conducted at the Manado State University Computer Center Building by conducting a case study where data would be collected, processed, and analyzed. The results showed that the ground resistance on the panel was 4.71 Ohm, and the ground resistance of the lightning rod was 3.10 Ohm. After redesigning using six electrodes, both for grounding the lightning rod and equipment, the value is 2.97 Ohms. The results of the analysis of how important the use of lightning rods in the Computer Center Building is, a score of 14 is obtained. These results conclude that a lightning rod system is needed in the Computer Center Building. Abstrak— Tujuan penelitian ini adalah untuk merancang sistem pentanahan di Gedung Pusat Komputer serta menganalisis kelayakan gedung dalam penggunaan sistem penangkal petir. Penelitian ini dilaksanakan di Gedung Pusat Komputer Universitas Negeri Manado dengan melakukan studi kasus dimana data akan dikumpulkan, diolah, dan dianalisa. Hasil penelitian menunjukan tahanan tanah pada panel sebesar 4,71 Ohm, tahanan tanah pada penangkal petir sebesar 3,10 Ohm. Setelah dilakukan perancangan kembali dengan menggunakan 6 batang elektroda, baik untuk pentanahan penangkal petir dan peralatan didapatkan nilai 2,97 Ohm. Hasil analisis mengenai seberapa pentingnya penggunaan penangkal petir di Gedung Pusat Komputer didapatkan nilai 14. Dari hasil tersebut disimpulkan bahwa sangat diperlukan sistem penangkal petir di Gedung Pusat Komputer.